2012
DOI: 10.1007/s10896-012-9424-6
|View full text |Cite
|
Sign up to set email alerts
|

TREAD: A Promising Change-Target for Partner Abuse Prevention with Adolescents

Abstract: There is consensus in the partner abuse prevention education literature that a skills-focus is needed. However, appropriate instruments for evaluating the effectiveness of skills-focused programs do not exist. Against this background, and based on the dyadic slippery slope model of partner abuse, the Tendency to Resist or End Abusive Dynamics (TREAD) scale was developed. TREAD is defined as one's tendency to respond assertively or protectively in situations involving warning-sign (potentially hurtful or contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…A 20 item questionnaire was developed for the purpose of the study, guided by research into emotional abuse. 1 The questionnaire and scales developed by Jacobson and Gottman (1998), Murphy and Smith (2010) and Murphy, Smith and Xenos (2012) were looked at most closely when generating and choosing individual warning sign behaviours and their domains. The behaviours included were based upon observations during therapeutic work with young women conducted by Murphy, and each behaviour used in the current study is one that she found to occur in abusive adolescent relationships, but that is not necessarily viewed as harmful by adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…A 20 item questionnaire was developed for the purpose of the study, guided by research into emotional abuse. 1 The questionnaire and scales developed by Jacobson and Gottman (1998), Murphy and Smith (2010) and Murphy, Smith and Xenos (2012) were looked at most closely when generating and choosing individual warning sign behaviours and their domains. The behaviours included were based upon observations during therapeutic work with young women conducted by Murphy, and each behaviour used in the current study is one that she found to occur in abusive adolescent relationships, but that is not necessarily viewed as harmful by adolescents.…”
Section: Methodsmentioning
confidence: 99%
“…A program of research conducted by K. A. Murphy and colleagues in Victoria, Australia, stands out as unique in its consideration of the subtle behavioral signs of partner abuse that are defined by young people and could be used in prevention programs. These authors take a dyadic view of the development of harmful dynamics in intimate relationships and define the early warning signs of abuse (warning sign behaviors [WSBs]) as “partner behaviours that have the potential to trigger dynamics characterized by secrecy, overdependence, anger or power imbalance” (K. A. Murphy, Smith & Xenos 2012, p. 352).They theorize that a “slippery slope” of seemingly innocent boundary transgressions may set a foundation for greater violations and potential later abuse (K.…”
Section: Warning Signs Of Ipamentioning
confidence: 99%
“…To measure the effectiveness of IPA prevention interventions with young people in high school settings, K. A. Murphy, Smith and Xenos (2012) developed and validated the Tendency to Resist or End Abusive Dynamics (TREAD) scale which assesses respondents’ perceptions of partner WSB and their proposed responses to it.…”
Section: Warning Signs Of Ipamentioning
confidence: 99%
See 2 more Smart Citations